A Dynamical Behavior Measurement Algorithm for Smart Meter Data: An Analytical Study - Al-Ghaili A.M.; Baskaran H.; Ibrahim Z.-A.; Rahim F.A.; Hairi S.A.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Data Analytics; Dynamics; Graph algorithms; Smart meters; Time series; Analysis evaluation; Analytical studies; Direct manipulation; Dynamical behaviors; Mathematical operations; Security issues; Network security